Evropská cesta a výpověď dopisů. Formování Sidneyho intelektuální osobnosti // Sidney’s continental tour and testimony of letters. Genesis of Sidney’s concept of poesy - Martina Kastnerová (Svět Literatury, 2017)
The study intends to investigate the relations between Philip Sidney and the continental intellectual circle (mainly that of Protestant scholars and aristocrats) on the basis of Sidney’s correspondence. The study is focused especially on the Czech cultural milieu. Sidney’s „grand tour“ over continent is crucial for the formation of his concept of poetry. The poesy is, against Sidney, among all forms of learning the best suited to move the soul to virtue through the beautiful and delightful images of moral example, playing its important role in society.